Impact of reimbursement program on liver‐related mortality in patients with chronic hepatitis B in Beijing, China. Issue 9 (21st July 2019) - Li, Min; Kong, Yuan Yuan; Wu, Shan Shan; Zhou, Jia Ling; Wu, Xiao Ning; Wang, Lin; Su, Jian Ting; Ou, Xiao Juan; You, Hong; Xie, Xue Qin; Wei, Zai Hua; Jia, Ji Dong
Abstract : Objective: Since July 1, 2011 antiviral therapy for hepatitis B virus infection has been listed as a reimbursable expense for medical insurance in Beijing. This study aimed to assess the impact of this program on liver‐related death for patients with chronic hepatitis B (CHB). Methods: Profiles of patients with CHB discharged between January 2008 and December 2015 were retrieved from the Beijing hospital discharge database. Liver‐related deaths in these patients occurring between January 2008 and December 2017 were retrieved by linking them to the death certification database. Liver‐related mortality (number of deaths divided by the observed person‐years) before and after this program was launched was calculated and compared. A Poisson regression was performed to assess the strength of association (risk ratio [RR]) between the reimbursement program and liver‐related mortality. Results: Information on 35 943 discharged patients (17 114 patients with non‐cirrhotic and 18 829 with compensated cirrhotic CHB) was retrieved. Altogether 3 832 liver‐related deaths during the 190 695 person‐years were observed. After the reimbursement program was launched, liver‐related mortality per 100 person‐years dropped from 0.38% to 0.16% for patients with non‐cirrhotic CHB, and from 4.03% to 3.39% for those with compensated cirrhosis. The program was associated with a lower risk of developing liver‐related death for patients with non‐cirrhotic CHB (RR 0.40, 95% confidence interval [CI] 0.30‐0.52) and those with compensated cirrhosis (RR 0.84, 95% CI 0.78‐0.89). Conclusion: Coverage of antiviral therapy by basic medical insurance reduced the risk of developing liver‐related death for patients with non‐cirrhotic and with compensated cirrhotic CHB.